Criminal Responsibility For Negligence In Dental Implants In Jordanian Legislation Preparation (Journal of Namibian Studies : History Politics Culture, 2023)
The background of the study is the dental profession, like any profession, which contains the so-called error and we cannot suggest that there are no medical errors in the dental profession, so this study combines the dentist's error in the dental implant procedure as one of the examples of medical errors, negligence and legal responsibility. This study combines dentistry on the one hand and the law on the other hand, therefore may turn to legal medicine in the field of dentistry, especially in dental implants in Jordanian legislation, and laying the foundations for the correct therapeutic medical procedure in the specialty of dental implants.Type of studies reviewed: Medical studies specialized in dental implants and focus on medical error in legal studies and the Jordanian Medical Liability Law of 2018 and some other Arab lawsThe Results: The existence of medical errors as a result of medical procedures that violate the principles of Dental profession in form of negligence should be exposed to criminal responsibility. The dentist's professional obligations encompass carelessness, insufficient precautionary measures, or failure to adhere to laws, rules, and directions, both prior to, during, and subsequent to the dental implant operation.